An annealing-free aqueous-processed anatase TiO2 compact layer for efficient planar heterojunction perovskite solar cells. Issue 79 (21st June 2017) - Yang, Chengwu; Yu, Mingyu; Chen, Dichun; Zhou, Yaqing; Wang, Wei; Li, Yang; Lee, Tung-Chun; Yun, Daqin
Abstract : We report efficient perovskite solar cells (PCE = 18.29 ± 0.18%) based on TiO2 films synthesised via a facile aqueous, annealing-free route. Abstract : A facile aqueous-based fabrication scheme is developed for producing annealing-free anatase TiO2 (AF-TiO2 ) films that exhibit efficient electron transport properties in planar heterojunction perovskite solar cells (PSCs). AF-TiO2 films are fabricated by spin coating on a substrate a colloidal solution of anatase TiO2 nanoparticles (NPs) prepared via a low temperature hydrolytic sol–gel method. The resultant AF-TiO2 films show low electrical resistance, high transmittance in the visible and near-infrared regions and facilitation of high-quality perovskite film formation, which can be attributed to their homogeneous surface morphology and nanocrystallinity. The AF-TiO2 based PSCs achieve a power conversion efficiency (PCE) of 18.29 ± 0.18%, showing significant improvement compared to the control PSCs (PCE = 11.33 ± 0.32%) based on TiO2 films made by high-temperature annealing of amorphous TiO2 (HTA-TiO2 ).